Kampus Mengajar 6 Belajar Sambil Berdampak di SD Negeri Buduran - Farsya Salsabila Putri (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Teaching Campus (Teaching Campus) is an activity carried out by the government to improve the level of education that has declined due to the COVID-19 pandemic. The outbreak of the COVID-19 pandemic has impacted the education process, which has been directed towards online or distance learning. This has resulted in a lack of interaction in face-to-face learning. The Kampus Mengajar program is motivated by the decline in learning, and Indonesia needs the assistance of students to optimize the learning process. Kampus Mengajar also provides opportunities for students to learn and develop themselves through activities conducted outside the campus or beyond classroom lectures. Kampus Mengajar is also designed to help promote equal education in Indonesia.